AT 2018cow VLBI: no long-lived relativistic outflow. Issue 4 (21st November 2019) - Bietenholz, Michael F; Margutti, Raffaella; Coppejans, Deanne; Alexander, Kate D; Argo, Megan; Bartel, Norbert; Eftekhari, Tarraneh; Milisavljevic, Dan; Terreran, Giacomo; Berger, Edo
ABSTRACT: We report on Very Long Baseline Interferometry (VLBI) observations of the fast and blue optical transient (FBOT), AT 2018cow. At ∼62 Mpc, AT 2018cow is the first relatively nearby FBOT. The nature of AT 2018cow is not clear, although various hypotheses from a tidal disruption event to different kinds of supernovae have been suggested. It had a very fast rise time (3.5 d) and an almost featureless blue spectrum, although high photospheric velocities (40 000 km s −1 ) were suggested early on. The X-ray luminosity was very high, ∼1.4 × 10 43 erg s −1, larger than those of ordinary supernovae (SNe), and more consistent with those of SNe associated with gamma-ray bursts. Variable hard X-ray emission hints at a long-lived 'central engine.' It was also fairly radio luminous, with a peak 8.4-GHz spectral luminosity of ∼4 × 10 28 erg s −1 Hz −1, allowing us to make VLBI observations at ages between 22 and 287 d. We do not resolve AT 2018cow. Assuming a circularly symmetric source, our observations constrain the average apparent expansion velocity to be 0.49 c by t = 98 d (3σ limit). We also constrain the proper motion of AT 2018cow to be 0.51 c . Since the radio emission generally traces the fastest ejecta, our observations make the presence of a long-lived relativistic jet with a lifetime of more than 1 month very unlikely.